Distinct Clinical Characteristics of Patients With Congenital Duodenal Obstruction in a Medical Center in Taiwan - Li-Yi Tsai; Wu-Shiun Hsieh; Chien-Yi Chen; Hung-Chieh Chou; Po-Nien Tsao; Wen-Ming Hsu (Pediatrics and Neonatology)
Patients with congenital duodenal obstruction (CDO) predominantly have a postampullary lesion site and a high association with Down syndrome, according to previous reports from Western countries. This study aimed to determine whether there are racial differences in the clinical characteristics of congenital duodenal obstruction, based on the experience from a Taiwanese medical center. Methods: The charts were retrospectively reviewed among neonates with CDO who received surgery at National Taiwan University Hospital during the period 1985- 2008. Patients were grouped into a preampullary or postampullary group according to the obstruction in relation to the ampulla of Vater. Other characteristics, including sex, time of diagnosis, operative findings, as well as associated anomalies, were recorded for further analysis. Results: A total of 30 patients with CDO including 16 with atresia, 10 with mucosal webs, and 4 with stenosis, were recruited; among them, 16 were boys and 14 were girls. In 15 patients (50%), the diagnosis of duodenal obstruction was made prenatally. A total of 11 of the 30 patients (37%) were in the preampullary group and 19 (63%) were in the postampullary group. Seventeen patients (56.7%) had at least one additional anomaly, including four (13%) who had trisomy 21. The preampullary group had significantly fewer associated congenital anomalies than in the postampullary group (27% vs. 74%, p = 0.012). Conclusion: Our cohort showed a relatively lower incidence of postampullary lesions and associated Down syndrome in patients with CDO compared with Western countries. Additionally, patients with preampullary lesions had significantly less association with other anomalies.